Winter study - Barr, Nevada (New York: Berkley Books, 2009)
Visiting an isolated Lake Superior isle to study wolf behavior, ranger Anna Pigeon joins a scientific group that subsequently discovers unusual DNA evidence suggesting that a giant and dangerous wolf hybrid has been introduced by an unknown source.
Keywords: Pigeon, Anna (Fictitious character) -- Fiction; Women park rangers -- Fiction; Wolves -- Fiction; Rocky Mountain National Park (Colo.) -- Fiction; Isle Royale (Mich.) -- Fiction; Mystery fiction